2002
DOI: 10.1016/s0166-2236(02)02063-5
|View full text |Cite
|
Sign up to set email alerts
|

Neural encoding of behaviourally relevant visual-motion information in the fly

Abstract: The goal of neuroethology is to explain behaviour in terms of the activity of nerve cells and their interactions. This can only be achieved if the experimental animal can be analysed at different levels ranging from behaviour to individual neurons. Cellular mechanisms underlying processing of neuronal information are frequently analysed using in vitro preparations where artificial stimulation replaces the natural sensory input. Although such studies provide fascinating insights into the complex computational a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 76 publications
0
109
1
Order By: Relevance
“…This aftereffect, the waterfall illusion, is not unique to humans: elegant behavioural work has shown that it is also experienced by flies (Götz & Wenking 1973;Srinivasan & Dvorak 1979), indicating that motion adaptation is also relevant to these animals (Clifford & Langley 1996). In flies, the physiological counterpart of this phenomenon can be found in motion-sensitive neurons in the third visual neuropile (lobula plate), most of which sum motion signals across large areas of visual space (Hausen 1984;Krapp & Hengstenberg 1996;Egelhaaf et al 2002). Similarly to macaque MT neurons (Kohn & Movshon 2003, these cells adapt their response characteristics to prolonged stimulation (Srinivasan & Dvorak 1979;Maddess & Laughlin 1985;de Ruyter van Steveninck et al 1986;Fairhall et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This aftereffect, the waterfall illusion, is not unique to humans: elegant behavioural work has shown that it is also experienced by flies (Götz & Wenking 1973;Srinivasan & Dvorak 1979), indicating that motion adaptation is also relevant to these animals (Clifford & Langley 1996). In flies, the physiological counterpart of this phenomenon can be found in motion-sensitive neurons in the third visual neuropile (lobula plate), most of which sum motion signals across large areas of visual space (Hausen 1984;Krapp & Hengstenberg 1996;Egelhaaf et al 2002). Similarly to macaque MT neurons (Kohn & Movshon 2003, these cells adapt their response characteristics to prolonged stimulation (Srinivasan & Dvorak 1979;Maddess & Laughlin 1985;de Ruyter van Steveninck et al 1986;Fairhall et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…We observed the same inseparabilities in the UV STRFs of L-neurons. This type of directional computation is distinct from that seen in fully opponent directionally selective cells, like lobula plate tangential cells in flies (Hausen, 1982a,b;Single et al, 1997;Borst and Haag, 2002;Egelhaaf et al, 2002) or complex cells in the mammalian visual cortex (Emerson et al, 1992) that encode directionality in the mean of the response.…”
Section: Discussionmentioning
confidence: 90%
“…A matched filter is a concept in neuroethology and describes the spatial layout of some population of receptors that is matched to a certain aspect of the task (Wehner 1987). For example, preferred directions for arrays of elementary motion detectors seem to corre- spond to flow fields induced by particular movements of flies, e.g., by roll movements (Egelhaaf et al 2002;Krapp 2000;Franz and Krapp 2000;Franz et al 2004). Our matched filters have the typical structure of flow fields for pure translations in the horizontal plane: a focus of expansion, a focus of contraction, and nearly horizontal flow between them (Fig.…”
Section: Homing With Two Flow Templatesmentioning
confidence: 99%